Wound healing potential of Majorana Hortensis and Curcuma Longa herbal gel in albino rats - K. LALITHA; P.SAILAJA RAO (International Journal of Pharma and Bio Sciences, 2018)
In developing countries the gradual revival of use of medicinal plants is attributed to the safety of herbal medicines with minimal adverse effects as comparable to the synthetic drugs. The present study was aimed to evaluate the wound healing effect of combination of extracts of Majoranahortensis and Curcuma longaherbal gel in wistar rats. As individual drugs they have been reported to have significant anti-bacterial, immunomodulatory and anti-inflammatory activities. Assuming that a combination will always possess more potent activity, an optimizedtopical gel (carbopol- 934, as gelling agent) formulation in combination with the two herbal drugs was prepared in the 2:3 ratio and was evaluated for wound healing activity. The individual herbs were evaluated for their standard specifications according to the herbal pharmacopoeia of India.The extracts were prepared using standard procedures and physico-chemical parameters of the formulated gel were determined. Wound healing activity of the formulated herbal gel containing M.hortensis and C.longa was compared with the standard nitrofurozone cream, using experimentally induced open wound model in albino wistar rats. The animals were divided into 5 groups of six in each group (n=6) and treated for a period of 21 days with formulated herbal gels of individual herbal extracts and in combination, choosing nitrofurazone cream as a standard preparation. The parameters like percent wound contraction and period of epithelisation were determined. From the results it has been found thatcombined formulated gel showed significant epithelisation period (*p<0.001) of 21.30 ± 0.47a days and the% wound contraction was 99.7a ± 0.082 possessing a significant wound healing activity.